Magnetic induction spectroscopy (MIS)—probe design for cervical tissue measurements. (27th April 2017) - Wang, Jau-Yi; Healey, Timothy; Barker, Anthony; Brown, Brian; Monk, Chris; Anumba, Dilly
Abstract: Objective: Gradiometers have the advantage of increasing measuring sensitivity, which is particularly useful in magnetic induction spectroscopy (MIS) for bio-impedance measurements. Traditional gradiometers use a pair of field sensing coils equally distant and on opposite sides of a drive coil, which provides high immunity to interference. In this paper, a ferrite-cored coaxial gradiometer probe of 29 mm diameter has been developed for measuring the impedance spectra of cervical tissues in vivo . Approach: It consists of a ferrite rod with outer ferrite confinement screening in order to eliminate the signals from surrounding tissue. The magnetic screening efficiency was compared with an air-cored gradiometer probe. For both gradiometer probes, a drive coil and two sensing coils were wound on a borosilicate glass former aligned coaxially with two sensing coils equidistant from the drive coil. The signal sensitivity of those two MIS gradiometers has been measured using saline samples with a conductivity range between 0.1 and 1.1 S m −1 . Finite element methods using COMSOL Multiphysics have been used to simulate the distribution of sensitivity to conductivity over the face of each probe and with depth. Main Results: The ferrite-cored probe has a sensitivity confined to the volume defined by the gap between the ferrite core and outer tube of ferrite while the air-cored probe without any magnetic shielding had a wide sensitivity over the face and the side of the probe. Four saline samples and one of distilled water with conductivities from 0.1 to 1.1 S m −1 have been used to make conductivity measurements at frequencies of 50 kHz, 100 kHz, and 300 kHz. The measurement accuracy of the air-cored MIS probe was 0.09 S m −1 at 50 kHz, improving to 0.05 S m −1 at 300 kHz. For the ferrite-cored MIS probe, the measurement accuracy was 0.28 S m −1 at 50 kHz, improving to 0.04 S m −1 at 300 kHz. Significance: In vivo measurements on human hand have been performed using both types of gradiometers and the conductivity is consistent with reported data.